Enhanced mechanical properties of Al0.43CoCrFeNi2.1 high entropy alloy fabricated through complex shear flow casting: Experiment and MD simulation - Simeng Jiang; Yaya Zhao; Weijie Fan; Weiyang Xie; Yanlin Wang; Xiaohua Chen; Zidong Wang (Journal of Materials Research and Technology)
In this study, a novel preparation method for high-entropy alloys (HEAs) was developed. Al0.43CoCrFeNi2.1 HEA ingots were cast under complex shear flow, while a comparison group was cast without applying shear flow. Various characterization techniques were employed to analyze the microstructural differences between the two samples. Molecular dynamics (MD) simulations were used to investigate the nucleation characteristics, microstructure evolution, and dislocation evolution during solidification. Additionally, to investigate the deformation properties and mechanical behavior of the two samples, uniaxial tension was applied to the solidified samples using MD simulations. The results reveal that by introducing severe shear flow, the equiaxed grains of the Al0.43CoCrFeNi2.1 HEA alloy were refined, twins were formed, and the likelihood of dislocation ring formation and dislocation entanglement during solidification decreased. Compared to the traditional method, the sample prepared by complex shear flow casting (CSFC) exhibits yield strength (YS), ultimate tensile strength (UTS), and elongation (EL) of 330.7 MPa, 661.7 MPa, and 54.8%, respectively, showing increases of 23.1%, 26.6%, and 7.5%, respectively. The strengthening and toughening mechanisms were discussed, suggesting that the refinement of equiaxed grains, the elimination of dislocation entanglement, the twinning-induced plasticity (TWIP) effect during deformation, and the transformation-induced plasticity (TRIP) effect induced by fivefold twins contribute to the improvement of mechanical properties. The novel CFSC method holds significant potential for applications in HEAs.